Preclinical syndromes predict dementia: the Sydney older persons study. Issue 3 (1st September 2001) - Waite, L M; Broe, G A; Grayson, D A; Creasey, H
Abstract : OBJECTIVES: To identify if preclinical syndromes for Alzheimer's disease, vascular dementia, and Parkinson's disease and related dementias exist. Identification of dementia at early or even preclinical stages has important implications for treatment. METHODS: A community dwelling sample of 647 subjects aged 75 and over at recruitment were followed up for a mean period of 3.19 years (range 2.61 to 4.51 years). Each subject was asked to participate in a medical assessment which included a standardised medical history examining both past and current health and medication usage; a neuropsychological battery (mini mental state examination, Reid memory test, verbal fluency, subsets of the Boston naming test and similarities, clock drawing and copied drawings) and physical examination. Preclinical syndromes for the three predominant dementias (Alzheimer's disease, vascular dementia and Parkinson's disease, and related dementias) and their combinations were defined using cognitive, motor, and vascular features. Their longitudinal outcome as defined by death and dementia incidence was examined. RESULTS: Preclinical syndromes affected 55.7% (n=299) of subjects. Preclinical syndromes showed a trend for an increased odds of death (odds ratio 1.72, p=0.056) and a significantly increased odds of developing dementia (odds ratio 4.81, p<0.001). Preclinical syndromes were highly sensitive, detecting 52 of 58 (89.7%) incident dementias. Two hundred and sixteen of 268 (80.6%) preclinical subjects did not show dementia over the 3 year period (positive predictive value 19.4%). Subjects defined as having a combination of cognitive, extrapyramidal, and vascular features were at greatest risk of progressing to dementia. CONCLUSIONS: Preclinical syndromes were sensitive and significant predictors of dementia. In view of their poor positive predictive value, the preclinical syndromes as defined in this study remain a research tool needing both definitional refinement and greater periods of observation. Multiple coexistent preclinical disorders resulted in a greater incidence of dementia, providing evidence for an additive role between multiple disorders.